1993
DOI: 10.1152/ajpgi.1993.265.4.g646
|View full text |Cite
|
Sign up to set email alerts
|

Gastric myoelectric and motor activity in dogs with gastric dilatation-volvulus

Abstract: Electrical and contractile properties of the stomach were assessed in six adult dogs after recovery from surgical treatment for gastric dilatation-volvulus (GDV), a disorder characterized by delayed gastric emptying of the solid phase. Electrodes and strain-gauge force transducers were sutured to the serosa of the antrum and pylorus at the time of surgical intervention for GDV. Ten days after implantation, electrical and mechanical activities were recorded before and after a standardized meal. The analog FM ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…In one study, antral dysrhythniias occurred during fasting state phase I in approximately 50 per cent of normal dogs when observed over three fasting myoelectric cycles (Gullikson and others 1980). To the authors' knowledge, antral dysrhythmias during the fed state have not been previously reported in normal dogs (Hall 1989).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In one study, antral dysrhythniias occurred during fasting state phase I in approximately 50 per cent of normal dogs when observed over three fasting myoelectric cycles (Gullikson and others 1980). To the authors' knowledge, antral dysrhythmias during the fed state have not been previously reported in normal dogs (Hall 1989).…”
Section: Discussionmentioning
confidence: 78%
“…Six implants were placed in each dog: four silver-wire bipolar electrodes and two strain gauge force transducers. The silver Electrodes were constructed in the laboratory (Hall 1989). The strain gauge force transducers were purchased (RB Products).…”
Section: Implantsmentioning
confidence: 99%
“…We did not find any difference in frequency of vomiting, diarrhoea, eructation or grass eating between control dogs and dogs with GDV; only more frequent defecation seems to be connected with a lower risk of GDV. This could be connected to the increased motility of the gastrointestinal tract, which is a possible pathogenic factor in GDV development (Hall et al 1993). A higher risk of GDV was found in dogs whose mother or father, but not offspring, suffered from GDV.…”
Section: Discussionmentioning
confidence: 97%
“…The aetiology of GDV is not yet known, but many predisposing factors have been described, including decreased gastric motility, inflammatory bowel disease or other signs of impaired gastrointestinal function (Hall et al 1993;Braun et al 1996;Beck et al 2006). Many studies have focused on the identification of endogenous and exogenous factors which may help in the identification of dogs at risk of GDV.…”
Section: Gastric Dilatation and Volvulus Syndrome (Gdv)mentioning
confidence: 99%
“…In addition, alterations in gastrointestinal motility have been thought to play a role in the development of GDV, although results are inconsistent. There is some evidence from myoelectrical studies that gastric motility is impaired after recovery from GDV (10); and in one study radiopaque markers mixed with solid food were emptied more slowly from the stomach in post-operative GDV dogs than in healthy dogs (9). However, it remains unclear, if impaired gastric emptying is a cause or consequence of GDV or if abdominal surgery and gastropexy have a permanent effect on gastric motility, an effect that could be shown in people (11).…”
Section: Introductionmentioning
confidence: 99%